Growth parameters and food frequently consumed by Basotho children aged 6–24 months old at Maseru and Leribe districts of Lesotho: A cross‐sectional study - Mothusi Nyofane; Malebusa Rapotsane; Mohlotsane Moshao (Pediatric Discovery)
Abstract Undernutrition in children remains a public health concern. Despite the global efforts to address undernutrition, Lesotho continues to bear the highest burden of childhood undernutrition. The study assessed the anthropometric measurements and dietary intake of children aged 6–24 months. A descriptive cross‐sectional study was conducted among 113 mother–child dyads attending clinic visits at Makoanyane Military Hospital (Maseru district); n = 50 and Motebang Hospital (Leribe district); n = 63. A structured sociodemographic and feeding practices questionnaires based on adapted World Health Organization (WHO) questionnaires were used. The usual food consumption was collected using an unquantified food frequency questionnaire. Anthropometric measurements and z scores computation were done as per WHO standard guidelines. Statistics included percentages for categorical variables and means for continuous variables. The percentage of continued breastfeeding was 54.0% in Maseru and 28.6% in Leribe districts. Complementary feeds were introduced at the mean age of 5.3 ± 1.0 (Maseru) and 5.2 ± 1.3 months (Leribe). In Leribe, 84.1% of children were consuming maize porridge every day while in Maseru, 68.0% of children were consuming commercial baby cereal every day. The prevalence of wasting was 10.0% (Maseru) and 20.6% with 14.3% of severe wasting (Leribe). A higher percentage of stunting was observed in Leribe (36.5%) than in Maseru (20.0%) (p < 0.001). The prevalence of moderate and severe stunting was 8.0% and 12.0% in Maseru and 20.6% and 15.9% in Leribe, respectively. The prevalence of stunting is alarmingly high in Leribe. The findings suggest an urgent need to strengthen maternal and child health and nutrition programs to ameliorate feeding practices and nutritional status.